Plato and democracy today - Lee, Keekok, 1938- (Newcastle upon Tyne, UK : Cambridge Scholars Publishing, 2018)
This book deploys an innovative narrative device to mount an exercise in (popular) political philosophy. It presents Plato as "the Reith Lecturer" bringing up to date his critique of democracy which he began more than two thousand years ago in The Republic. --
Incluye referencias bibliográficas (páginas 155-171) índice.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Plato -- Political and social views; Democracy; Libros electrónicos.